2022
DOI: 10.1002/cam4.4560
|View full text |Cite
|
Sign up to set email alerts
|

A novel LASSO‐derived prognostic model predicting survival for non‐small cell lung cancer patients with M1a diseases

Abstract: Introduction:The current American Joint Committee on Cancer (AJCC) M1a staging of non-small cell lung cancer (NSCLC) encompasses a wide disease spectrum, showing diverse prognosis. Methods: Patients who diagnosed in an earlier period formed the training cohort, and those who diagnosed thereafter formed the validation cohort. Kaplan-Meier analysis was performed for the training cohort by dividing the M1a stage into three subgroups: (I) malignant pleural effusion (MPE) or malignant pericardial effusion (MPCE); (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…This study shows that with increasing age, the prognosis is worse, and the study by Chen et al et al [6] also confirmed this view. With the advances in LC screening technology and treatment drugs, [20] the survival rate of MLUAD patients has improved.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This study shows that with increasing age, the prognosis is worse, and the study by Chen et al et al [6] also confirmed this view. With the advances in LC screening technology and treatment drugs, [20] the survival rate of MLUAD patients has improved.…”
Section: Discussionsupporting
confidence: 74%
“…Interestingly, LUAD patients with different metastatic sites have different prognoses, with median OS ranging from 3 to 8 months, which suggests that MLUAD is highly heterogeneous. [ 5 , 6 ] Therefore, the prognosis of patients with MLUAD varies greatly.…”
Section: Introductionmentioning
confidence: 99%
“…The nomogram has the advantage of being a visual tool and incorporating more clinical characteristics and are widely applied in oncology ( 15 17 ). In this study, information on advanced pancreatic ductal adenocarcinoma in patients aged ≥50 years was obtained from the SEER database.…”
Section: Introductionmentioning
confidence: 99%